Brutaliser la pythie - Manfred Lesgourgues (Cahiers Mondes Anciens)
The transgression consisting in using violence to force the Pythia of Delphi to give an oracle is attested around three distinct historical figures from the Classical and Hellenistic periods: Philomelos the Phocidian, Alexander the Great and Appius Claudius Pulcher. By contextualizing their respective actions and showing that these are indeed three distinct events and not the revival by ancient historians of the same motive, the present article analyses the strategies of instrumentalization of violence that each of them uses to assert their power.